A Framework for Cloud-based Energy Evaluation and Management for Sustainable Decision Support in the Built Environments. (2015) - Cho, Yong K.; Li, Haorong; Park, JeeWoong; Zheng, Keke
Abstract: This paper introduces a framework which can advance traditional building auditing and energy management methods in terms of cost, convenience of automatic and remote data (e.g., 3D geometry and thermal values) collection, system control, and comprehension and dissemination of results using a proposed cloud-based software as a service (CSaaS) system as a decision support tool. The decision support tool can help decision makers improve their buildings by providing reliable and visualized information of the building's energy performance through an easy-to-use interactive virtual evaluation system in a publicly accessible cyberspace. The proposed open decision-support platform is expected to ultimately reduce the public's energy consumption and invigorate the nation's economy by vitalizing sustainable product manufacture and retrofit construction industries.